Iterative learning control for repetitive tasks with randomly varying trial lengths using successive projection - Zhuang, Zhihe; Tao, Hongfeng; Chen, Yiyang; Stojanovic, Vladimir; Paszke, Wojciech (1975- )
This article proposes an effective iterative learning control (ILC) approach based on successive projection scheme for repetitive systems with randomly varying trial lengths. A modified ILC problem is formulated to extend the classical ILC task description to incorporate a randomly varying trial length, while its design objective considers the mathematical expectation of its tracking error to evaluate the task performance.
Keywords: iterative learning control; optimal control; nonuniform trial length